Keabsahan Risalah Lelang Atas Objek Lelang Yang Tidak Dapat Dibalik Nama - Junaidi, Muhammad; Wibowo, Tri; Ratna Sediati, Diah Sulistyani; Arifin, Zaenal; Soegianto, Soegianto (Universitas Semarang, 2023)
The study aims to analyze the validity of the auction bulletin and the constraints and solutions made by the Office of Auctions on the object of the auction that cannot be renamed. The process of execution of the auction has been regulated in this way by various laws and regulations. In practice, there are some cases where the auction object cannot be renamed, even though the auctions have been carried out in accordance with the conditions and have been made by the Auction Office. The type of research used in this investigation is normative jurisprudence with a method of legislative approach. As a result, in the event that there is an auction object that cannot be named after, it does not immediately result in the following auction process: The auction notice made by the auction office becomes invalid. For example, the case in the decision of the Central Java High Court No. 161/PDT/2016/PT.SMG dated July 15, 2016. The Supreme Court's judgment recognizes the validity of the Auction, although the judgement leads to legal uncertainty for the auction vendor and KPKNL Semarang. In order to establish the basis of legal certainty and the foundation of justice for the seller and KPKNL Semarang, it is recommended to file a lawsuit and settlement to the state court to ensure the status and legal status of the post auction process that has taken place. The novelty of this research is the study of the Auction Records on an auction object that cannot be renamed.Penelitian ini bertujuan untuk menganalisis keabsahan Risalah Lelang beserta kendala dan solusinya yang dibuat oleh Pejabat Lelang atas objek lelang yang tidak dapat dibalik nama. Proses pelaksanaan lelang telah diatur sedemikian rupa dalam berbagai peraturan perundang-undangan. Begitu juga dengan proses balik nama atas objek lelang, telah diatur dalam peraturan perundangan dengan jelas. Dalam praktiknya, terdapat beberapa kasus bahwa objek lelang tidak dapat dibalik nama meskipun lelang telah dilaksanakan sesuai ketentuan dan telah dibuat Risalah Lelang oleh Pejabat Lelang. Jenis penelitian yang digunakan dalam penelitiaan ini adalah yuridis normatif dengan metode pendekatan perundang-undangan. Hasilnya, dalam hal terdapat objek lelang yang tidak dapat dibalik nama, tidak serta merta mengakibatkan proses lelang berikut Risalah Lelang yang dibuat oleh Pejabat Lelang menjadi batal dan tidak sah. Sebagai contoh, kasus dalam putusan Pengadilan Tinggi Jawa Tengah Nomor 161/PDT/2016/PT.SMG tanggal 15 Juli 2016. Dari putusan pengadilan tinggi tersebut keabsahan Risalah Lelang tetap diakui, meskipun dengan adanya putusan tersebut mengakibatkan adanya ketidakpastian hukum bagi penjual lelang dan KPKNL Semarang. Guna mewujudkan asas kepastian hukum dan asas keadilan bagi penjual dan KPKNL Semarang, disarankan untuk mengajukan gugatan dan penetapan kepada pengadilan negeri untuk memastikan kedudukan dan status hukum atas proses pasca lelang yang telah terjadi. Kebaruan penelitian ini yaitu kajian tentang Risalah Lelang atas objek lelang yang tidak dapat dibalik nama.